2012
DOI: 10.1210/en.2012-1135
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Rasd1 Expression by Glucocorticoids and Prolactin Controls Peripartum Maternal Insulin Secretion

Abstract: The transition from gestation to lactation is characterized by a robust adaptation of maternal pancreatic β-cells. Consistent with the loss of β-cell mass, glucose-induced insulin secretion is down-regulated in the islets of early lactating dams. Extensive experimental evidence has demonstrated that the surge of prolactin is responsible for the morphofunctional remodeling of the maternal endocrine pancreas during pregnancy, but the precise molecular mechanisms by which this phenotype is rapidly reversed after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Of note, recent studies on Elavl4/HuD describe its role in regulating translation of the insulin mRNA, and transgenic overexpression in mice resulted in impaired insulin release (40). Furthermore, inhibition of Rasd1 was shown to result in increased insulin release in MIN6 cells (41). Taken together, these results indicate targets of miR-375 can either positively or negatively influence secretion, and therefore only after the identification of all targets can we reach an understanding of the complexity of its role in the ␤-cell.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent studies on Elavl4/HuD describe its role in regulating translation of the insulin mRNA, and transgenic overexpression in mice resulted in impaired insulin release (40). Furthermore, inhibition of Rasd1 was shown to result in increased insulin release in MIN6 cells (41). Taken together, these results indicate targets of miR-375 can either positively or negatively influence secretion, and therefore only after the identification of all targets can we reach an understanding of the complexity of its role in the ␤-cell.…”
Section: Discussionmentioning
confidence: 99%
“…Both AGS1 and Rhes have an extended carboxyl terminus as compared with Ras family proteins, and both proteins interact with G i /G o and regulate G protein signaling (Cismowski et al, , 2000Graham et al, 2002Graham et al, , 2004Takesono et al, 2002;Vargiu et al, 2004;Nguyen and Watts, 2005;Harrison and He, 2011). AGS1 has a range of functional roles, including inhibition of cell growth, N-methyl-D-aspartate receptor signaling, regulation of the circadian rhythm, and regulation of hormone secretion (Fang et al, 2000;Graham et al, 2001;Jaffrey et al, 2002;Takahashi et al, 2003;Cheng et al, 2004;Vaidyanathan et al, 2004;Lellis-Santos et al, 2012;McGrath et al, 2012;Chen et al, 2013;Harrison et al, 2013). Rhes …”
Section: Activators Of G Protein Signaling: Mechanistic and Functionamentioning
confidence: 99%
“…Another study reported that dexamethasone increased the protein expression of Rasd1 in pancreatic b-cells and diminished insulin secretion. 35 These studies indicated that Rasd1 and TRPC4 could be common molecular candidates in controlling insulin secretion in b-cells (Fig. 4).…”
Section: The Roles Of Glucocorticoids and Leptin Via Trpc4 In Insulinmentioning
confidence: 91%
“…In pancreatic b-cell, dexamethasone decreased insulin secretion while mRNA level of Rasd1 was shown to be increased. 35 The upregulation of Rasd1 expression by glucocorticoids was due to glucocorticoid response element (GRE) in the 3'-flanking region of the human Rasd1 gene. 36 Rasd1 has all of the conserved domains of the Ras superfamily required for guanine nucleotide binding, hydrolysis, and effector interaction.…”
Section: Trpc4 Channelsmentioning
confidence: 99%
See 1 more Smart Citation